Synopsis of the genus Capnia (Plecoptera: Capniidae) from China - Li, Weihai; Yang, Ding (Zootaxa, 2009)
A winter stonefly species of the family Capniidae, Capnia qilianshana sp. nov., is described as new to science from Gansu, China. Its relationship with closely related species is discussed. An unassociated female based on a single specimen from Sichuan province is presented.